Analisis Penerapan User Fee untuk Pemanfaatan Sumberdaya Perikanan Demersal - Akhmad Fauzi Syam; Moch Prihatna Sobari; Sri Dharmayanti (Buletin Ekonomi Perikanan, 2003)
The alternative Instrument to reach the need of fisheries development other than conventional Instrument Is User Fee or Ashing Fee. The advantage In developing fisheries using Fishing Fee is that It take Into account many aspect especially economy and technology for each kind of fishermen. This study attempt to calculate the proper fee for [demersal] fishermen In Muara Angke, North Jakarta. The study shows that user fee Is able to be Implemented In Muara Angke In the term of maximum economic yield. The result also shows that the [demersal] fishermen In Muara Angke Is not suitable yet for implementation of user fee, caused by their Inefficiency.